Ratio Legis Integrated Law Enforcement Centre (Gakkumdu) in the Electoral Law Enforcement System - Rahman, Kholilur; Jamil; Arifin, Samsul; Zairuddin, Ahmad (Journal of Development Research, 2025)
Compared to other legal regime issues, the issue of election law can be said to be more complex. In addition to the numerous categories of problems, the implementation of handling election law issues also involves many institutions, such as Gakkumdu, which consists of Bawaslu (Election Supervisory Board), the Public Prosecutor's Office, and the Police. This research is interesting to discuss because it deals with matters of authority related to institutional prestige, which may give rise to institutional controversies that deserve attention. Some of the discussions that will be addressed are the issue of ratio legislation or the foundation for the establishment of Gakkumdu and its position in enforcing criminal election laws. Furthermore, the urgency of Gakkumdu's authority in the process of enforcing criminal election laws and their problems will be discussed. The research method used is normative, employing a statutory approach and a conceptual approach. The research findings conclude that, first, the ratio legis aims to achieve the principle of coordination to align the understanding and handling patterns of election-related crimes among Bawaslu, the Police, and the Public Prosecutor's Office. Second, Gakkumdu plays a crucial role in enforcing criminal election laws, which requires a prompt enforcement process. However, there are often problems in its enforcement, one of which is the lack of shared perception and agreement among Bawaslu, the Police, and the Public Prosecutor's Office in handling election-related criminal cases.